2023
DOI: 10.1007/s10461-022-03971-4
|View full text |Cite|
|
Sign up to set email alerts
|

A Capacity-Strengthening Intervention to Support HIV Pre-exposure Prophylaxis (PrEP) Awareness-Building and Promotion by Frontline Harm Reduction Workers in Baltimore, Maryland: A Mixed Methods Evaluation

Abstract: Pre-exposure prophylaxis (PrEP) is a promising but underutilized HIV prevention tool among people who inject drugs (PWID). We developed and piloted an intervention to bolster PrEP promotion competencies among frontline harm reduction workers (FHRW) serving PWID clients in Baltimore, Maryland. Between December 2021 and February 2022, we developed and facilitated four trainings, which included didactic and practice-based/role-playing components, with 37 FHRW from four organizations. FHRW completed three structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Finally, another study that combined fictional client personas, role-play exercises, and focused on providing information on PrEP effectiveness, prescribing practices, and service delivery, demonstrated increased PrEP knowledge and self-efficacy among Baltimore HIV clinicians. 19 Similarly, the evaluation of our training showed improvements in learners' knowledge, comfort, skills, and capacity to provide PrEP, as well as scalability of PrEP provision posttraining.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Finally, another study that combined fictional client personas, role-play exercises, and focused on providing information on PrEP effectiveness, prescribing practices, and service delivery, demonstrated increased PrEP knowledge and self-efficacy among Baltimore HIV clinicians. 19 Similarly, the evaluation of our training showed improvements in learners' knowledge, comfort, skills, and capacity to provide PrEP, as well as scalability of PrEP provision posttraining.…”
Section: Resultsmentioning
confidence: 68%
“…Trainees were less likely to express frustration with challenging cases and reported more confidence in sexual history taking, improved skills in assessing readiness for change, and increased support in their clinical setting. Finally, another study that combined fictional client personas, role‐play exercises, and focused on providing information on PrEP effectiveness, prescribing practices, and service delivery, demonstrated increased PrEP knowledge and self‐efficacy among Baltimore HIV clinicians 19 . Similarly, the evaluation of our training showed improvements in learners' knowledge, comfort, skills, and capacity to provide PrEP, as well as scalability of PrEP provision posttraining.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies have also identified limited PrEP awareness or inaccurate information on PrEP among PWID [34][35][36][37][38]. To improve awareness, one study leveraged existing rapport with harm reduction providers to improve accuracy of PrEP knowledge among PWID [35].…”
Section: Discussionmentioning
confidence: 99%
“…To improve PrEP knowledge among PWID, we recommend educational programs that target them. These programs should include the dissemination of PrEP education in various media platforms such as social and mass media, as well as information leaflets and billboards ( 22 ). HCWs should provide PrEP knowledge to PWID when they are being attended for other health problems, including drug addiction rehabilitation services ( 23 ).…”
Section: Strategies To Address the Barriers To Oral Prep Use Among Pwidmentioning
confidence: 99%
“…HCWs should provide PrEP knowledge to PWID when they are being attended for other health problems, including drug addiction rehabilitation services ( 23 ). PrEP education programs should also involve peer educators, especially those who have been successfully rehabilitated since they may be trusted by PWID ( 22 ). We recommend that the provision of PrEP knowledge should include information about the common side effects of oral PrEP, as well as address the misconceptions and myths about oral PrEP.…”
Section: Strategies To Address the Barriers To Oral Prep Use Among Pwidmentioning
confidence: 99%